Dynamic propeller conformation for the unprecedentedly high degree of chiral amplification of supramolecular helices - Kim, Taehoon (Royal Society of Chemistry, 2016)

(untitled) (Chem Sci)
An unprecedentedly high degree of chiral amplification of supramolecular helices in a sergeants and soldiers system was realized using a propeller-shaped molecule, triphenylamine (TPA), as the monomer. One sergeant controlled the handedness of 500 soldiers in supramolecular helices. We further demonstrated that a TPA derivative could switch its role from sergeant to soldier and vice versa depending on its partners. These achievements could be realized using the dynamic propeller conformation of TPA and provide new insights into supramolecular assemblies and the supramolecular chiral amplification of helices.